Wind farms have cascading impacts on ecosystems across trophic levels. Issue 12 (December 2018) - Thaker, Maria; Zambre, Amod; Bhosale, Harshal
Abstract Wind farms are a cleaner alternative to fossil fuels for mitigating the effects of climate change, but they also have complex ecological consequences. In the biodiversity hotspot of the Western Ghats in India, we find that wind farms reduce the abundance and activity of predatory birds (for example, Buteo, Butastur andElanus species), which consequently increases the density of lizards, Sarada superba . The cascading effects of wind turbines on lizards include changes in behaviour, physiology and morphology that reflect a combination of predator release and density-dependent competition. By adding an effective trophic level to the top of food webs, we find that wind farms have emerging impacts that are greatly underestimated. There is thus a strong need for an ecosystem-wide view when aligning green-energy goals with environment protection. In the Western Ghats of India, the presence of wind farms is found to reduce the abundance and activity of predatory birds, with the associated effect of increasing the density of lizard prey and altering lizard behaviour and physiology.